Penerapan higher order thinking skills (HOTS) pada pembelajaran pendidikan kewarga negaraan (PKN) di madrasah ibtidaiyah - Fani Zahriana Dwizar; Abdul Gani Jamora Nasution (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This article has the aim of analyzing the application of Hots-based PKN learning at MIS Al Mahabbah. To reveal the results achieved, researchers used a qualitative approach, with data collection methods of interviews, observation, and documentation. Then, to ensure the validity of the data is used through triangulation. The research results obtained as follows. First, the application of Hots in PKN learning has been found through lesson plans, teachers already have insight into Hots and the implementation of Hots-based learning is often used by teachers. Second, there are still obstacles in carrying out Hots learning such as determining learning designs, class management and making evaluations (tests). Third, solutions made by teachers with peer-sharing actions, learning design innovations including apperception, and studies on making test questions. Also, in the implementation of motivational learning and explanation of the learning scheme in more detail.